Benjamin Franklin's humor - Zall, Paul M. (University Press of Kentucky, 2005)
Humor is sometimes a serious business, especially the humor of Benjamin Franklin, a master at revealing the human condition through comedy. For the country's bicentennial, Reader's Digest named Franklin "Man of the Year" for embodying the characteristics we admire most about ourselves as Americans-humor, irony, energy, and fresh insight. Recreating Franklin's words in the way that his contemporaries would have read and understood them, Paul M. Zall chronicles Franklin's use (and abuse) of humor for commercial, diplomatic, and political purposes. Dedicated to the uniquely appealing and endurin